TINJAUAN SEJARAH HUKUM PASAL 33 UUD 1945 SEBAGAI IDEOLOGI EKONOMI (THE LEGAL HISTORY REVIEW OF ARTICLE 33 UUD 1945 AS ECONOMIC IDEOLOGY) - Fadli Zon; Muhammad Iskandar; Susanto Zuhdi (Jurnal Negara Hukum: Membangun Hukum Untuk Keadilan, 2016)
Article 33 of the 1945 Constitution is intended by its drafters as the economic ideology of Indonesia. It contains the idea of economic sovereignty as complement to the political independence of Indonesia. As a formulation containing an ideological notion, it should be understood through comprehensive tools of thinking, along the multi-disciplinary mode of thinking that constitutes the background of its formulation. A number of economists involved in the process of the amendment of the article has failed to comprehend its position and status. This essay is a historical overview of the position of Article 33 of the 1945 Constitution and the nature of Indonesian way of thinking. ABSTRAKPasal 33 UUD 1945 dimaksudkan oleh perumusnya sebagai ideologi ekonomi Indonesia. Di dalam pasal tersebut terkandung gagasan mengenai kedaulatan ekonomi untuk melengkapi kemerdekaan politik Indonesia. Sebagai rumusan yang mengandung gagasan ideologis, Pasal 33 seharusnya dipahami dengan perangkat pemikiran yang komprehensif, sejalan dengan multidisiplin-pemikiran yang telah melatarbelakangi penyusunannya. Sejumlah ekonom yang terlibat dalam proses perubahan Pasal 33 UUD 1945 gagal memahami posisi dan kedudukan pasal tersebut. Artikel ini merupakan tinjauan sejarah hukum atas kedudukan Pasal 33 UUD 1945 di dalam konstitusi dan alam pikir keindonesiaan.